Natural occurrence of Alternaria mycotoxins in malting barley grains in the main producing region of Argentina - Castañares, Eliana (2019)
Background: Barley (Hordeum vulgare L.) is one of the most important cereals worldwide, and its quality is affected by fungal contamination such as species of the genus Alternaria. No information is available about the occurrence of Alternaria mycotoxins in Argentinean barley grains, which is of concern, because they can be transferred into malt and beer. The aim of this study was to analyze the occurrence of alternariol (AOH), alternariol monomethyl ether (AME) and tenuazonic acid (TeA), in malting barley grains from the main producing regions of Argentina during 2014 and 2015 growing seasons. Results: The most frequent mycotoxin was AOH (64 %), and was detected in higher levels (712 μg Kg‐1) compared to other studies, followed by TeA (37 %, 1522 μg Kg‐1), while AME was present in five samples in the 2015 growing season only, with a mean of 4876 μg Kg‐1. A similar frequency of mycotoxin occurrence was observed in both years (80.8 % vs. 85.3 %), but a more diverse contamination was found in 2015, which was characterized by lower accumulated precipitation. Nevertheless, AOH was more frequently found in 2014 than in 2015 (80.8 % and 47.1 %, respectively). A negative correlation between AOH concentration and temperature was observed. The susceptibility of different barley varieties to mycotoxin accumulation varied with the mycotoxin, geographical location and meteorological conditions. Conclusion: The results obtained in the present work represent a tool for risk assessment of the exposition to these mycotoxins and could be used by food safety authorities to determine the need of their regulation. Furthermore, the establishment of a HACCP system to minimize fungal and mycotoxin contamination in barley from farm to processing could be apply to ensure food safety.